7x - 2(x + 6) = -2, simply the equation
7x -2x - 12 = -2, expand
5x - 12 = -2, combine like terms
5x = 10, add 12 to the other side
x = 2, divide by five
x = 2, that wasn't so bad now? hope this helps
2007-10-23 10:47:44
·
answer #1
·
answered by --- 3
·
0⤊
0⤋
x=2
2007-10-23 10:47:05
·
answer #2
·
answered by lakewoodskater308 1
·
0⤊
0⤋
7x - 2(x + 6) = -2
first distribute the -2 the integers in the parenthesis
7x - 2x -12 = -2
combine like-terms
5x - 12= -2
add the 12 to the -2
5x= 10
divide the 5 by the 10
x= 2
TADA!!!!!!!
2007-10-23 10:49:50
·
answer #3
·
answered by justme 3
·
0⤊
1⤋
5 x - 12 = - 2
5x = 10
x = 2
2007-10-24 04:17:56
·
answer #4
·
answered by Como 7
·
1⤊
0⤋
7x - 2x - 12 = -2
5x = 10
x = 2
2007-10-23 11:59:56
·
answer #5
·
answered by ♥♥felisha♥♥ 5
·
0⤊
0⤋
7x -2x -12 = -2
5x = 10
x =2
2007-10-23 10:46:48
·
answer #6
·
answered by shirah d 2
·
0⤊
0⤋
7x - 2x - 12 = -2
5x = 10
x = 2
2007-10-23 10:46:04
·
answer #7
·
answered by CPUcate 6
·
0⤊
0⤋
7x - 2(x+6)= -2
7x - 2x + 12 =-2
5x + 12 = -2
5x/5 +12 = -2/5
x+ 12 = -0.4
- 12 -12
x = -12.4
2007-10-23 10:52:38
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
solve for x
expand the equation---7x-2x-12=-2
put all the x's on one side and all the other crap to the other side by subtracting adding dividing multiplying, which ever one is needed---7x-2x=-2+12
simplify the expression---5x=10
and now solve for x by adding subtracting multiplying or dividing, in this case dividing---x=2
and thats your answer.
2007-10-23 10:48:44
·
answer #9
·
answered by rochesmk 2
·
0⤊
0⤋
did u know the answer it = 2 ha
2007-10-23 10:48:33
·
answer #10
·
answered by bangjbig 1
·
0⤊
0⤋